Ready set rogue - Collins, Manda (Collins, Manda. Studies in scandal novel., 2017)
When scholarly Miss Ivy Wareham receives word that she's one of four young ladies who have inherited Lady Celeste Beauchamp's estate with a magnificent private library, she packs her trunks straightaway. Unfortunately, Lady Celeste's nephew, the rakish Quill Beauchamp, Marquess of Kerr, is determined to interrupt her studies one way or another... Bequeathing Beauchamp House to four bluestockings -no matter how lovely they are to look at -is a travesty, and Quill simply won't have it. But Lady Celeste's death is not quite as straightforward as it first seemed -and if Quill hopes to solve the mystery behind her demise, he'll need Ivy's help. Along the way, he is surprised to learn that bookish Ivy stirs a passion and longing that he has never known. This rogue believes he's finally met his match -but can Quill convince clever, skeptical Ivy that his love is no fiction?